Characteristics of unsteady excitation induced by cavitation in axial-flow oil–gas multiphase pumps. (April 2018) - Liu, Xiaobing; Hu, Quanyou; Wang, Huiyan; Jiang, Qifeng; Shi, Guangtai
The unstable cavitation flow and the dynamic characteristics of oil-gas multiphase pumps usually lead to vibration, noise, and even pump damage. The multiphase flow mixture model and the full cavitation model were used to simulate the transient flow and dynamic features of the pump. The results show that cavitation changes the inflow conditions, aggregates the unstable flow, and generates large pressure pulsations. It also accelerates the variation frequency of axial force and intensifies the uneven distributions of internal flow and circumferential pressure. Both the radial force on the impeller and its variation amplitude are enlarged. Understanding the characteristics of unsteady excitation induced by cavitation can provide references for studying the mechanism of vibration and noise in multiphase pumps.